Improving content, organization, vocabulary, language use, and mechanics using Movie Trailer Media - Nehru Pasoloran Pongsapan; Andi Anto Patak (International Journal of Evaluation and Research in Education (IJERE), 2021)
Writing implicates conveying or communicating ideas or thoughts obliges the media either in conventional (paper and pen) or digital material (computer). This research applied a pre-experimental approach with one group pretest and post-test design. The independent variable is movie trailers as teaching media. The dependent variable is students' writing skills consist of content, organization, vocabulary, language use, and mechanics. This research indicated a significant difference in writing skills before and after the treatment using movie trailers with narrative text. There were 30 writing class students participated in this research; hence, they are homogeneous. Students seemed to be more encouraged to learn more about writing skills with enjoyable and relaxing strategies. This research signposted significant impact on the movie trailer's usage of writing skills’ improvement. Movie trailers could be used as one of the learning media to foster students' resolution in telling stories in writing based on the imagination that comes after watching. Therefore, this research recommends using a movie trailer as one strategy to improve the students' writing ability.